AN ANALYSIS OF THE ENTREPRENEURIAL POTENTIAL IN OLTENIA TOURIST REGION - Ionuţ Cosmin BĂLOI (Management & Marketing)
Tourism can bring an attractive horizon for Romania: the projects can generate jobs, cooperation between the touristic destinations, the increase of living standards and local people revenues. This paper treats an issue of tourist business administration and seeks to assess the actual potential of tourist resources and determining the differences between the Oltenia's actual touristic exploitation and their growth potential. We develop a model of evaluate the tourist resources, the industry efficiency and also their attractiveness for entrepreneurial initiatives. Their quantification can be statistically correlated leading to a rethinking of models that shape the parameters of regional competitiveness. The synthetic and the graphic tools highlights the most important features of the competitiveness of tourism for the region of Oltenia.